Pengaruh Perbandingan Tepung Tulang Ikan Tuna Sirip Kuning (Thunnus albacares) dan Terigu Terhadap Karakteristik Cookies Sebagai Makanan Fungsional Tinggi Kalsium - Septiyani Irawan, Azizah; Indri Hapsari Arihantana, Ni Made; Sugitha, I Made (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 12 No 3 (2023): Jurnal ITEPADO - 10.24843/itepa.2023.v12.i03.p11, 2023)
The purpose of this study was to determine the effect of comparison yellowfin tuna fish bone and wheat flour on the characteristics of cookies and to determine the best comparison of yellowfin tuna fish bone to produce cookies with the best characteristics. The design used in this study was a completely randomized design (CRD) with treatment of the amount of flour and bone meal of yellowfin tuna consisting of 5 levels, that are 100%: 0%; 90%:10%; 80%:20%; 70%:30%; and 60%:40%. The treatment was repeated 3 times to obtain 15 experimental units. The data obtained were analyzed statistically using variance and if the treatment had a significant effect, it was continued with Duncan's Multiple Distance Test. The results showed that the ratio of flour and bone meal of yellowfin tuna had a significant effect on water content, ash content, protein content, fat content, carbohydrate content, calcium content, scoring test (color, texture, aroma, and taste) and hedonic test (color, aroma, and texture) cookies. Ratio of 60% flour with 40% yellowfin tuna fish bone produced cookies with the best characteristics with the criteria of water content 6.5%, ash content 13.17%, protein content 11.54%, fat content 46.85%, carbohydrates content 21.90%, calcium content 5.91%, characteristic of colour was brownish yellow and ordinary, aroma was fishy and ordinary, texture was crunchy and ordinary, taste was slightly typical of tuna and ordinary, and overall acceptance was ordinary.